Age Related Change in Morphometric Study of Normal Lumbar Intervertebral Disc by MRI in A Tertiary Hospital of Bangladesh - Reza, Rumela; Ashrafuzzaman, Md; Zahur, Tamanna; Fatema, Sharmin; Bhowmick, Baishakhi; Chowdhury, Kakoli (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: Magnetic resonance imaging is the most widely used method of specifically assessing intervertebral disc degeneration. The present study was aimed to evaluate morphology of lumbar intervertebral disc at different vertebral level in relation to age of normal individuals of Bangladeshi population of Chattogram district. Materials and methods: This cross-sectional observational study was conducted in the Department of Anatomy, Chittagong Medical College, Chattogram, during the period April 2021 to March 2022 upon 50 male and 50 female by dividing them into five age groups according to decade. For statistical analysis ANOVA test was done and p-value was considered significant if it was <0.05 at 95% level of confidence. For significant ANOVA test post hoc was done. Results: The age of the respondents ranged from 30-79 years with the mean ± SD was 43.50±12.61year. The mean of SL and IL compared with different age group which was highly significant (p <0.01). ADH, MDH and PDH were observed to differ among different age group but statistically was not significant (p > 0.05) when ANOVA test was performed. Conclusion: The morphometry of lumbar intervertebral disc might be considered during the surgical reconstruction for the treatment of lumbar spine diseases and for the medical manufacturers to make proper surgical devices for the Bangladeshi population. JCMCTA 2022 ; 33 (2) : 72-78